Sustentabilidade em propriedades rurais: um estudo na área de proteção ambiental de Santana do Livramento/RS - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The present research aimed to understand the concept of sustainability expressed by the small producers living in Ibirapuitã APA in Santana do Livramento, RS, and to describe how they incorporate the productive practices developed in their properties. For the accomplishment of this study a research of applied nature was developed, qualitative approach, characterized as descriptive and exploratory regarding the objectives. Data were collected through in-depth interviews with seven respondents. The study revealed that several interviewees present an empirical knowledge about the concepts of sustainability and Environmental Protection Area, but somehow develop them instinctively. In the researched properties there are areas exclusively directed to preservation, not being developed any type of activity with commercial purpose in this space. There is also evidence of the need for greater circulation of information about what is allowed to be done within the properties, since many individuals are not aware of how to proceed. Key-words: Sustainability. Environmental Protection area. Sustainable Production.
Keywords: Sustentabilidade; Área de proteção ambiental; Produção Sustentável; Sustainability; Environmental protection area; Sustainable production; CNPQ::CIENCIAS SOCIAIS APLICADAS